Considering Section 7.1, suppose we began the analysis to find E = E1+ E2with two cosine functions E1= E01cos (Ït + α1) and E2= E02 cos (Ït + α2). To make things a little less complicated, let E01= E02 and α1 = 0. Add the two waves algebraically and make use of the familiar trigonometric identity cos θ + cos Φ = 2 cos 1/2 (θ + Φ) cos 1/2 (θ + Φ) in order to show that E = E0cos (Ït + α), where E0= 2E01cos α2/2 and α = α2/2. Now show that these same results follow from Eqs. (7.9) and (7.10).
Enjoy 24/7 customer support for any queries or concerns you have.
Phone: +1 213 3772458
Email: support@gradeessays.com